The Value of Lived Experience With the Criminal Justice System: A Qualitative Study of Peer Re-entry Specialists - González, Jennifer M. Reingle (International journal of offender therapy and comparative criminology, 2019)
The aim of this article was to describe the implementation and qualitative outcomes of peer reentry specialists ("peers") on housing attainment, mental health, and substance use problems, and increased life domain functioning. One-on-one interviews were conducted with peers and clients to understand the program implementation, peer experiences, and progress toward target outcomes. Data were iteratively coded using inductive thematic identification and data reduction. Results suggest that peers' lived experiences were useful in building rapport with clients. Peers applied their lived experiences to assist clients in seeking treatment for substance use and mental health conditions, in addition to helping them locate housing and employment. Several structural barriers prevented peers from addressing client needs. Peer time was routinely consumed by assisting clients in seeking identification, requisite for treatment or use of health care services, housing or securing employment. Findings suggested peers were working to address many client needs. Future research should examine the effectiveness of peer assistance on client-level health outcomes, including recidivism.